Optimalisasi Kontribusi Data Call Center 110 Dalam Mendukung Pemolisian Prediktif Pada Era Police 4.0 : di Wilayah Hukum Polda Metro Jaya - Pambudi, Raditya Wahyu Aji (Prisani Cendekia Institute, 2025)
This study aims to analyze the contribution of data from the Call Center 110 to predictive analysis and detection of crime patterns, analyze factors that influence the contribution of Call Center 110 data in supporting predictive policing, and analyze efforts to optimize the contribution of Call Center 110 data in supporting Predictive Policing in the Police 4.0 Era in the jurisdiction of Polda Metro Jaya. This study uses a qualitative approach with a case study method and data collection techniques through interviews, document studies, and observations. This study uses predictive policing theory, routine activity theory, collaborative policing theory, SOSTAC communication theory, Call Center 110 concept, and Police 4.0 concept. Data analysis techniques use data reduction, data presentation, and data verification. The findings show that the contribution of Call Center 110 data in predictive analysis and crime pattern detection in the Police 4.0 era at Polda Metro Jaya allows the use of big data and AI technology to process public reports to identify crime trends more accurately. Integration with AI-based CCTV systems, ANPR, and GIS allows mapping of crime-prone areas and the development of more effective predictive patrol strategies. Supporting factors for the success of this system include technological advances, digitalization policies, increasing human resource capacity, and collaboration between agencies. However, limited infrastructure, privacy issues, inconsistent data quality, internal resistance, and lack of coordination can hinder its implementation